The level of including digital literacy skills in the mathematics textbook for the first intermediate grade in KSA - Aldobyan, Ahood Hamad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to investigate the level of inclusion of digital literacy skills in the mathematics book for the first intermediate grade in the Kingdom of Saudi Arabia, and to achieve the objectives of the study, the descriptive analytical approach (the method of content analysis) was used, and the tool used in the analysis was a content analysis card consisting of (12) indicators. They are divided into three main axes (information literacy skills, media literacy skills, technology and communication culture skills). As for the research community and its sample, it consisted of a mathematics book for the first intermediate grade for the first and second semesters of 1442 AH, and the study concluded that the level of inclusion of mathematics books for the first grade is intermediate for cultural skills As a whole, digital skills came at a low rate (20.1%), as the skill in the mathematics book for the first semester was (24.5%), while the percentage of availability in the mathematics book for the second semester was (15.69%). Recommendations that curriculum designers should pay attention to embedding digital literacy skills in mathematics books for general education stages so that they contribute to providing learners with digital literacy skills, spreading awareness of the media and digital literacy skills in the educational field for students, mathematics teachers and parents, in addition to preparing training programs that help mathematics teachers to include digital literacy skills during lesson planning.
Keywords: digital literacy skills; media literacy; information literacy; information and communication culture; intermediate mathematics book